2012
DOI: 10.1117/1.jrs.6.063558
|View full text |Cite
|
Sign up to set email alerts
|

Classifying increaser species as an indicator of different levels of rangeland degradation using WorldView-2 imagery

Abstract: The development of new multispectral sensors with unique band settings is critical for mapping the spatial distribution of increaser vegetation species in disturbed rangelands. The objective of this study was to evaluate the potential of WorldView-2 imagery for spectral classification of four increaser species, namely Hyparrhenia hirta, Eragrostis curvula, Sporobolus africanus, and Aristida diffusa, in the Okhombe communal rangelands of South Africa. The 8-bands were extracted from the WorldView-2 image, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Each tree contributes a single vote for the assignment of the most frequent class to the input data. 28,30 The default number of trees (ntree) is usually 500, while the default value for the number of variables (mtry) is p P, where P equals the number of predictor variables within a data set. 29 First, RF builds many binary classification trees (ntree) using several bootstrap samples with replacements drawn from the original observations.…”
Section: Random Forest Classifiermentioning
confidence: 99%
“…Each tree contributes a single vote for the assignment of the most frequent class to the input data. 28,30 The default number of trees (ntree) is usually 500, while the default value for the number of variables (mtry) is p P, where P equals the number of predictor variables within a data set. 29 First, RF builds many binary classification trees (ntree) using several bootstrap samples with replacements drawn from the original observations.…”
Section: Random Forest Classifiermentioning
confidence: 99%
“…Among these satellites, WV-2 and WV-3 offer key spectral bands like yellow, coastal blue, and red edge that help in depicting tree characteristics. The utility of WV-2 image, for instance, has been demonstrated in various studies that include among others, predicting and mapping forest structural parameters [28], mapping of tree species [29], monitoring plantation forest [30], mapping increaser and decreaser grass species in degraded rangelands [31], and the detection of invasive alien plants [32]. These studies discussed the utility of the eight available spectral bands of WV-2 imagery and concluded that the WV-2 data have considerably improved the classification and prediction accuracies of features of interest compared to other multispectral data.…”
Section: Introductionmentioning
confidence: 99%